Rekonstruksi Dewan Perwakilan Daerah Sebagai Upaya Memperkuat Cheks and Balances di Lingkup Legislatif - Sunardi, Sunardi (Constitutional Law Review, 2023)
The main problem of this paper is how to strengthen the Regional Representative Council towards the implementation of the representation system in Indonesia and how to prevent the interference of political parties against Regional Representative Concil institutions. This problem is analysed using a normative and conseptual legal approach and is qualitative study. The Regional Representative Council has very limited authority causes the Regional Representative Council to not be able to contribute optimally to the development of democracy in Indonesia, especially in terms of regional development as the basis for Regional Representative Council representation in parliament. The Regional Representative Council also has the potential to be undermined and interfered with by the interests of political parties, due to the absence of statutory regulations that frmly and explicitly regulate the prohibition of the entry of political parties into the Regional Representative Council. This causes and interest conflict between the interests of political parties and their independence as regional representatives for Regional Representative Council members who come from political parties.